Growth of Rucola on Mars soil simulant under the influence of pig slurry and earthworms - Wamelink Gerrit Willem Wieger; Schug Line; Frissel Joep Yolanda; Lubbers Ingrid (Open Agriculture, 2022)
To feed humans on a future Mars settlement, a sustainable closed agricultural ecosystem is a necessity. On Mars, both the faeces of astronauts as well as any plant residues or other organic waste needs to be (re)used to fertilise the present regolith. The activity of earthworms may play a crucial role in this ecosystem as they break down and recycle the dead organic matter. The contribution of worms to Mars regolith forming is yet an unexplored territory. The first goal of our research was to investigate whether earthworms (Caligonella genus and Dendrobaena veneta) can survive in Mars soil simulant. The second goal was to investigate whether earthworm activity on Mars soil simulant can stimulate the growth of crops, in our case Rucola. The third goal was if earthworm activity can enhance the effect of pig slurry on the growth of Rucola. In a 75-day greenhouse experiment, we sowed Rucola in Mars soil simulant as well as in silver sand as an Earth control, amended with pig slurry, plant residues, and earthworms. During the experimental period, we observed worm activity. At the end of the experiment, the worms had propagated both in the Mars soil simulant and Earth control. However, we found no significant effect of worm activity on plant biomass production. This was probably due to the relative short duration of the experiment, being one life cycle of Rucola. Adding pig slurry stimulated plant growth significantly as expected, especially for the Mars soil simulant.